Challenges in evaluating associations among vasopressors, enteral nutrition, and nonocclusive mesenteric ischemia - Angela L Bingham; Brian L Erstad (American Journal of Health-System Pharmacy, 2026)
Abstract Purpose Acute mesenteric ischemia is a potentially life-threatening condition resulting from thromboembolic occlusion or nonocclusive mechanisms such as vasospasm and excessive vasoconstriction. Nonocclusive mesenteric ischemia (NOMI) is of particular concern in critically ill patients receiving vasopressors and enteral nutrition (EN). This paper reviews the challenges in evaluating associations among vasopressors, EN, and NOMI and discusses the pharmacist’s role in supporting patient-specific nutrition decisions during hemodynamic instability. Summary Mesenteric ischemia most commonly involves the superior mesenteric artery and carries high mortality. Diagnosis relies primarily on computed tomographic angiography because early recognition is difficult due to nonspecific signs such as ileus, abdominal pain, and lactic acidosis. Experimental and observational data suggest vasopressors may reduce mesenteric blood flow, with pharmacovigilance analyses demonstrating associations between several vasoactive agents and acute mesenteric ischemia. However, randomized controlled trials to establish these associations are lacking. Evidence evaluating early EN in patients with shock shows low reported rates of bowel or mesenteric ischemia (generally 0%-2%). Large randomized trials found higher rates of gastrointestinal complications, including rare cases of bowel ischemia, with full-dose EN but found similar mortality in patients receiving EN and those receiving parenteral nutrition (PN). Observational data suggest cautious EN may be feasible at lower vasopressor doses, though definitions of hemodynamic stability vary. Current guidelines recommend withholding EN during uncontrolled shock but provide limited detail regarding vasopressor thresholds for EN initiation or dosing modifications. Pharmacists can contribute by evaluating vasopressor exposure, recognizing patient-specific factors that may increase concern for gastrointestinal intolerance or ischemia, and participating in interprofessional decisions regarding EN initiation, advancement, and reassessment. Conclusion NOMI is uncommon but serious in critically ill patients. The relationships between vasopressors, EN, and NOMI remain uncertain due to diagnostic challenges and limited high-quality comparative data. Clinical decisions should be individualized, with vigilance in at-risk patients.